Cost implications of treatment non-completion in a forensic personality disorder service - Sampson, Christopher James; James, Marilyn; Huband, Nick; Geelan, Steve; McMurran, Mary (John Wiley & Sons, Ltd, 2013)
Background A high proportion of individuals admitted to specialist secure hospital services for treatment of personality disorder do not complete treatment. Non-completion has been associated with poorer treatment outcomes and increased rates of recidivism and hospital readmission, when compared with individuals who do complete treatment or who do not receive treatment at all.